A novel reopenable clip with sharp claw for complete closure of mucosal defects after colorectal endoscopic submucosal dissection - Yoshida, Naohisa; Hirose, Ryohei; Dohi, Osamu; Inagaki, Yoshikazu; Murakami, Takaaki; Inada, Yutaka; Morimoto, Yasutaka; Kobayashi, Reo; Inoue, Ken; Ghoneem, Elsayed; Itoh, Yoshito (Endoscopy, 2024)
The MANTIS Closure Device (MCD; Boston Scientific, Marlborough, Massachusetts, USA) is a reopenable clip with a sharp claw used for closure after endoscopic submucosal dissection (ESD). We evaluated the effectiveness of the MCD for fast and complete closure after colorectal ESD.Cases involving closure with the MCD after ESD of 20–60-mm colorectal lesions between April 2023 and January 2024 were reviewed. The primary end point was complete closure of the ESD defect with the MCD. Secondary end points included closure time, delayed bleeding, delayed perforation, and post-ESD coagulation syndrome (PECS). MCD application involved: 1) grasping the mucosa on the anal-side of the defect; 2) pushing the clip toward the oral-side mucosa and deploying it; 3) adding other reopenable clips for complete closure.61 cases involving MCD were analyzed. Mean tumor size was 32.3 (SD 9.2) mm. Complete closure rate was 98.4% and mean closure time was 6.9 (SD 2.6) minutes. The mean number of MCDs and other clips used was 1.0 (SD 0.1) and 4.7 (SD 1.4), respectively. Rates of delayed bleeding, delayed perforation, and PECS were 0%, 0%, and 9.8%, respectively.Fast and complete closure after colorectal ESD was successfully achieved using the MCD.